Economic globalization : issues, challenges, and responses by developing economics - National Conference on Economic Globalization : Issues, Challenges, and Responses By Developing Economics (1992 : Langkawi, Kedah); Universiti Utara Malaysia (Sintuk : UUM, 1992)
36